Pengaruh Penggunaan Media Sosial Tiktok Dalam Proses Pembelajaran - Renata Nur Annisa; Dinie Anggraeni Dewi; Santi Nurhayati (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
Technological progress at this time is very rapid. Technological developments that are often used are very widespread in society. The use of social media is very accessible to the general public. One of them is the social media Tiktok, there are already very many people who use the TikTok application as mere entertainment. Most people make the TikTok application a money-making application. Not only adults, but many small children have also used the application. Of course, the TikTok application has an impact on the learning process of children at school. The practical learning process in the classroom is very influential on student learning outcomes. The influence of social media on student performance will have positive or negative impacts.